2014
DOI: 10.3906/zoo-1401-2
|View full text |Cite
|
Sign up to set email alerts
|

First report of some parasites from Mediterranean mussel, Mytilus galloprovincialis Lamarck, 1819, collected from the Black Sea coast at Sinop

Abstract: This is the first study on parasite fauna of Mytilus galloprovincialis Lamarck, 1819 in Turkish waters. Mussel samples were collected monthly at 3 sampling stations on the coast of Sinop on the Black Sea in the period between August 2012 and July 2013. A total of 1740 mussels were examined for parasites using standard parasitological investigation procedures. The parasites identified included the following: 2 protozoans, Nematopsis legeri (32.12%) and Peniculistoma mytili (6.72%); 1 turbellarian, Urastoma cypr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…All locations differ from each other with respect to their ecologically properties; İskele region is a polluted area due to human activities at the inner harbor, Adabaşı region is the most natural and unpolluted area and the last region Sarıada is a site under the effect of both human activities and seasonal fresh water flowing which lowers the salinity level of the water. Details about the collection of mussels and laboratorial processes of parasite identification can be found in [17]. Temperature, Salt, Phosphate-PO4 and Nitrate-NO3 measurements were included to the models as biotic factors; and Sex, Condition Index-CI (i.e.…”
Section: Datamentioning
confidence: 99%
“…All locations differ from each other with respect to their ecologically properties; İskele region is a polluted area due to human activities at the inner harbor, Adabaşı region is the most natural and unpolluted area and the last region Sarıada is a site under the effect of both human activities and seasonal fresh water flowing which lowers the salinity level of the water. Details about the collection of mussels and laboratorial processes of parasite identification can be found in [17]. Temperature, Salt, Phosphate-PO4 and Nitrate-NO3 measurements were included to the models as biotic factors; and Sex, Condition Index-CI (i.e.…”
Section: Datamentioning
confidence: 99%
“…The presence of this parasite was noted from Black Sea, Sinop coast, Turkey [11, 12 and 5], and from Aveiro Lagoon, Portugal [3] in Mediterranean mussels. The trematode parasite Parvatrema duboisi was also reported from the gill filaments of the Mediterranean mussel in Black Sea, Sinop, Turkey [5]. Karagiannis et al [4] conducted a study in order to understand the presence of some parasitic disease and mortality problems in aquaculture system.…”
Section: Introductionmentioning
confidence: 99%
“…Its introduction, culture and transfer to different geographic areas increase the risks of spreading their parasites and diseases around the world (Francisco et al , 2010). Diseases in molluscs caused by parasites have been documented worldwide and Mytilus galloprovincialis has been reported to be infected by several parasites, including the protozoan Nematopsis legeri and Peniculostoma mytili , the turbellarian Urastoma cyprinae , the polychaeta Polydora ciliata and the trematode Parvatrema duboisi (Machkevsky, 1989; Murina & Solonchenko, 1991; Bower et al ., 1994; Robledo et al ., 1994; Belofastova, 1996, 1997; Caceres-Martinez et al ., 1998; Comps & Tige, 1999; Holodkovskaya, 2002; Francisco et al ., 2010; Machkevsky et al ., 2011; Özer & Güneydağ, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bataller & Boghen (2000) reported that the visible presence of the worms on the gills, especially when occurring in the hundreds and even thousands, could cause a decrease in demand by the lucrative half-shell market. Urastoma cyprinae has a wide distribution area including the Black Sea, having been recorded in several bivalve species including M. galloprovincialis from both cultured and natural beds (Fleming et al ., 1981; Goggin & Cannon, 1989; Noury-Srairi et al ., 1990; Murina & Solonchenko, 1991, Caceres-Martinez et al ., 1998; Özer & Güneydağ, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation